-6r-3=9r+12

Simple and best practice solution for -6r-3=9r+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6r-3=9r+12 equation:


-6r-3=9r+12

We simplify the equation to the form, which is simple to understand
-6r-3=9r+12

We move all terms containing r to the left and all other terms to the right.
-6r-9r=+12+3

We simplify left and right side of the equation.
-15r=+15

We divide both sides of the equation by -15 to get r.
r=-1

See similar equations:

| 2(f+3)+(2-5)+4f=6+6f | | 5a-3=5(a+1)+11a+6 | | 7x+8-9x=-2 | | 2x^1+4=0 | | -5p+20= | | 11-11m=40 | | j-7=2/7j+8 | | 0.5x+0.4(10)=0.3(x+30) | | 2x^2-40x+144=0 | | 3x+17=10x-25 | | log(3)*(x+4)+log(3)*(x-4)=2 | | 5(2x+6)+4=10x+34 | | -13d-4d-d-9d-7d=16 | | -3(-9)3y=-9 | | 1.3t-10.1t+7=13.24 | | -27x^2-36x-63=0 | | 2(3w)+2w=72 | | 2(x+4)=7x-22 | | 19x=169 | | t-1.6=-4.2 | | 11-6(3m-10)=5(4-m) | | 16+5n=45-56n | | 25-5x-7=2x-x | | log[2](x-4)-log[2](x+4)=3 | | y+3(6y+4)=12(y+1)+5y | | 9x^2-12x-21=0 | | x^2-(5+k)x+36=0 | | log(6)*(5x-3)=3 | | -5r-4=6r+51 | | 4h+7h-16=16 | | 6m=2(7m+28) | | 19=p-(-6) |

Equations solver categories